Exogenous nutrient inputs restructure phytoplankton community and ecological stoichiometry of Eastern Indian Ocean. (August 2021) - Zhou, Yuping; Yang, Xue; Wang, Ying; Li, Fangfang; Wang, Jiangtao; Tan, Liju
Graphical abstract: Highlights: Atmospheric deposition and upwelling increase nitrogen budget of tropical seas. Nitrogen inputs enhanced carbon flux through promoting primary productivity. The competition for nutrients caused the regime shift from cyanobacteria to diatom. The C/N ratio would alter along with changed nutrient status and community structure. Abstract: Exogenous nutrient inputs increasingly impact the structure and function of marine food weds through abiotic and biotic ways. The influence of nutrient inputs from atmospheric depositions and intermediate seawater supply on the phytoplankton growth and stoichiometry was studied in the Eastern Indian Ocean through multifactorial mesocosm experiments. Our results indicate that nitrogen inputs from atmospheric deposition and hydrodynamic processes did not only promote chlorophyll a biomass (5.3–58.52 μg·L -1 ) to increase the photosynthetically fixed carbon content but also generate a regime shift from picophytoplankton cyanobacteria to microphytoplankton diatom indicated by high relative abundance of microphytoplankton (>50%). These alternations of nutrient status and phytoplankton community structure reduced biodiversity of marine ecosystems (N-cultures, 0.18 to 0.56; control, 0.63) and generated the attendant C/N ratio of 5.6 ± 0.2 in cultures with nitrogen addition that was significantly lower than cultures with only phosphorus or iron addition. These results provide a thorough insight about the influence of nutrient inputs on marine biogeochemical cycle. Considering the universality of phytoplankton community alteration induced by exogenous nutrient inputs, integrating community compositions with phytoplankton stoichiometry may be helpful for clarify mechanisms of environment events impacting marine food weds.